The predatory and foraging efficiency of the predator Dicrodiplosis manihoti Harris , Diptera: Cecidomyiidae for some roles of the citrus mealybug Planococcus citri (Risso), Hemiptera: Pseudococcidae (Journal of the College of Basic Education, 2022)
This study was conducted in the laboratories and climate rooms of the Bio-control unit college of Agriculture / Baghdad University to investigate the most important biological indicators . During the course of this study, the predator proved to be an effective natural enemy of the mealy bug. Results revealed that its larval stages consumed an average of 4.37, 32.88 and 79.66 of the prey eggs respectively while 3.33, 17.66, and 69.33 for crawlers respectively. Consumption of adult of 1.5, 2.6 and 3.83 prey females respectively. The results showed a significant decline in the research efficiency of ravenous as the predator densities increased due to convergence as well as the role of cannibalism; therefore, the Wright determination of predator release rate will be of major important issue to control the target pest.